Phraseology in Interdisciplinary Research - Svět v obrazech a ve frazeologii II / The world in pictures and in phraseology 2. Ladislav Janovec (ed.). Praha: Univerzita Karlova, 2021. 552 s. ISBN 978-80-7603-201-9 - Korina, Natalia (Slavica, 2022)
A critical review of the scientific anthology Svět v obrazech a ve frazeologii II [The world in pictures and in phraseology 2] published in 2021 in Prague (ed. L. Janovec) presents and introduction in its contents and structure to the presented approaches to phraseology research. Mostly pragmatical, cultural linguistic and communicative orientation of the anthology confirms the relevance of interdisciplinary approaches in linguistics. The papers are being considered in the context of actual trends in linguistics, including wide interdisciplinary parallels and critical analysis of certain tendencies.